SOCIAL CLASS IN BRITISH SOCIETY IN JANE AUSTEN’S PRIDE AND PREJUDICE - Mira Andrea Putri; Syamsul Bahri; Rita Suswati (State University of Medan, 2017)
This study deals with social class in British society in Jane Austen’s Pride and Prejudice. The objectives of this study were to find out the impacts of social class toward british society based on the novel Pride and Prejudice written by Jane Austen and to describe social class reflected toward british society in that novel. The study was conducted by using descriptive qualitative method. The data of this research were dialogues and narration in Pride and Prejudice novel. The analysis of this study was based on Marxist’s concept (1995:25). The findings of this study were (1) two impacts of social class toward british society found in Pride and Prejudice novel, they were pride and prejudice (2) three types of social classes which were reflected, such as power, wealth, and status.